Observation of unusual chlorine activation by ground-based infrared and microwave spectroscopy in the late Arctic winter 2000/01 - Blumenstock, T.; Kopp, G.; Hase, F.; Hochschild, G.; Mikuteit, S.; Raffalski, U.; Ruhnke, R. (European Geosciences Union, 2006)
During the Arctic winter of 2000/01, ground-based FTIR and millimetre-wave measurements revealed significant amounts of ClO over Kiruna after the final warming in February 2001. In fact, column amounts of ClO were still increased in March 2001 when temperatures were about 20K above the PSC (Polar Stratospheric Clouds) threshold. At these temperatures, chlorine activation due to heterogeneous processes on PSCs is not possible even in the presence of strong lee wave effects. In order to discuss possible reasons of this feature, time series of other chemical species will be presented and discussed, too. Measurements of HF and COF2 indicated that vortex air was still observed in mid-March 2001. Since the time series of HNO3 column amounts do not give any evidence of a denitrification later than 11 February, chlorine activation persisting for several weeks after the presence of PSCs due to denitrification is rather unlikely. The photolysis of ClONO2-rich air which had been formed at the end of February and beginning of March 2001 as well as chlorine activation due to the presence of an unusual aerosol layer are discussed as possible causes of the increased ClO column amounts after the final warming.